The Influence of Financial Statement Quality, Corporate Governance, and Capital Structure on Company Value with Profitability as a Mediating Variable - Sari, Titis Nistia (West Science Accounting and Finance, 2025)
This study examines the effect of financial statement quality, corporate governance, and capital structure on firm value in Indonesia, with profitability serving as a mediating variable. Using a quantitative approach, data were collected from 165 companies across multiple industrial sectors through a structured Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to assess both direct and indirect relationships among variables. The findings reveal that financial statement quality and corporate governance have a positive and significant effect on firm value, whereas capital structure has a negative and significant effect. Profitability also plays a mediating role, strengthening the relationships between financial statement quality and corporate governance with firm value, but not between capital structure and firm value. These results confirm that transparent financial reporting, effective governance practices, and prudent capital management collectively enhance profitability and contribute to long-term value creation. The study provides empirical evidence that supports Agency Theory, Trade-Off Theory, and the Resource-Based View (RBV) in explaining firm value formation in emerging markets such as Indonesia. The practical implications emphasize the importance of improving governance mechanisms, financial reporting quality, and profitability strategies to increase investor trust and market valuation.